2007
DOI: 10.1177/0891241606293141
|View full text |Cite
|
Sign up to set email alerts
|

Subjects, Subjectivity, and Subjectification in Call Center Work

Abstract: In postindustrial society, paid labor is increasingly characterized as tertiary labor rather than primary or secondary labor and commonly mediated by computer and telecommunication technologies. However, there are few ethnographic studies on the production of the subject and subjectivity in postindustrial workplaces. This article reports a poststructurally informed ethnographic research in four telephone call centers, focusing on how technological and managerial practices are deployed and continuously oriented… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
12
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…That is, we can learn and grow to understand how their values allow them to be a group with unique characteristics that make them both socially and culturally valuable for themselves as people-what they want, what they value, and how they value it. We can also begin to learn how what we do from a strictly etic orientation affects them in ways that might alter their selves in ways that affect what they value-their subjectivity (Winiecki, 2004(Winiecki, , 2006(Winiecki, , 2007a(Winiecki, , 2007bWiniecki & Wigman, 2007).…”
Section: Value Of and For The Emicmentioning
confidence: 99%
“…That is, we can learn and grow to understand how their values allow them to be a group with unique characteristics that make them both socially and culturally valuable for themselves as people-what they want, what they value, and how they value it. We can also begin to learn how what we do from a strictly etic orientation affects them in ways that might alter their selves in ways that affect what they value-their subjectivity (Winiecki, 2004(Winiecki, , 2006(Winiecki, , 2007a(Winiecki, , 2007bWiniecki & Wigman, 2007).…”
Section: Value Of and For The Emicmentioning
confidence: 99%
“…Because findings of previous studies have been obtained across so many contexts, the present study was undertaken to expand consideration of the number of justice dimensions to the call center industry. Winiecki (2007) made note of a number of procedures employed in the call center industry to assess employees' work. Technologies are typically employed to monitor the pacing and sequencing of work and to assess the quality of interactions with customers.…”
mentioning
confidence: 99%
“…They note that "[t]here are thus other, more personal sources of identity work than organizational discourses, social identities and roles"(Sveningsson and Alvesson, 2003, p. 1168). Research on call centres has also demonstrated how developing identities at work through workplace practices can also be means through which individuals can be governed(Winiecki, 2006;Winiecki, 2007;Winiecki and Wigman, 2007). The focus here has been in the private sector.Context has also been shown to matter when conducting investigations about the formation of identity.…”
mentioning
confidence: 99%
“…Winiecki's (2007) study of call centre workers Winiecki (2007). contacted management to look to connect with a good participant, which in turn lead to interviews, an observation of that participant at work and a further recommendation of another potential participant from this original participant (p. 355).…”
mentioning
confidence: 99%
See 1 more Smart Citation